African Lightning and its Relation to Rainfall and Climate Change in a Convection‐Permitting Model. Issue 23 (24th November 2020) - Finney, D. L.; Marsham, J. H.; Wilkinson, J. M.; Field, P. R.; Blyth, A. M.; Jackson, L. S.; Kendon, E. J.; Tucker, S. O.; Stratton, R. A.
Abstract: Global climate models struggle to simulate both the convection and cloud ice fundamental to lightning formation. We use the first convection‐permitting, future climate simulations for the lightning hot spot of Africa, at the same time utilizing an ice‐based lightning parametrization. Both the model and observations show that lightning over Africa's drier areas, as well as the moist Congo, have more lightning per rainfall than other regions. Contrary to results in the literature, the future projection shows little increase in total lightning ( 10 7 flashes (or 2%) per degree warming). This is a consequence of increased stability reducing the number of lightning days, largely offsetting the increased graupel and updraft velocity driving an increase in lightning per lightning day. The next step is to establish if these results are robust across other models and, if combined with parametrized‐convection models, whether ensemble‐based information on the possible responses of lightning to climate change can be investigated. Plain Language Summary: Lightning depends on ascending air in thunderstorms and the collision of cloud ice particles, which charge the thundercloud. Many climate models have too coarse a resolution to reliably capture these processes. We focus on Africa, which has some of the most frequent lightning in the world. We use a model that is much higher resolution than usual, and this allows us to explicitly simulate the deep convection associated with thunderstorms as well as provide more detailed representation of the distribution of cloud ice particles. Our results show that in drier regions, as well as the much wetter Congo, there is relatively more lightning per kilogram of surface rainfall than there is in other parts of the continent. Lightning does increase across the continent under climate change, but by a relatively small amount. This is despite the number of days with lightning decreasing as the lower atmosphere becomes more stable. On days with lightning, there are more lightning flashes because there is an increase in cloud ice and intensity of convection. This study gives much more detailed information about African lightning than previous work. However, it is a single simulation. Future research should look at these results across other climate models. Key Points: Lightning and its relationship to rainfall vary considerably across Africa, with indication of dry lightning in arid regions Opposite changes in lightning days and intensity lead to little change in total flashes under climate change, unlike many past studies Graupel increases are smaller than column water increases, and therefore, lightning intensity mostly increases less than rain intensity